Postpartum Visit Attendance Increases the Use of Modern Contraceptives. (13th December 2016) - Masho, Saba W.; Cha, Susan; Charles, RaShel; McGee, Elizabeth; Karjane, Nicole; Hines, Linda; Kornstein, Susan G.
Abstract : Background. Delays in postpartum contraceptive use may increase risk for unintended or rapid repeat pregnancies. The postpartum care visit (PPCV) is a good opportunity for women to discuss family planning options with their health care providers. This study examined the association between PPCV attendance and modern contraceptive use using data from a managed care organization. Methods. Claims and demographic and administrative data came from a nonprofit managed care organization in Virginia (2008–2012). Information on the most recent delivery for mothers with singleton births was analyzed ( N = 24, 619). Routine PPCV (yes, no) and modern contraceptive use were both dichotomized. Descriptive analyses provided percentages, frequencies, and means. Multiple logistic regression was conducted and ORs and 95% CIs were calculated. Results. More than half of the women did not attend their PPCV (50.8%) and 86.9% had no modern contraceptive use. After controlling for the effects of confounders, women with PPCV were 50% more likely to use modern contraceptive methods than women with no PPCV (OR = 1.50, 95% CI = 1.31, 1.72). Conclusions. These findings highlight the importance of PPCV in improving modern contraceptive use and guide health care policy in the effort of reducing unintended pregnancy rates.